Cloning of an insecticidal cholesterol oxidase gene and its expression in bacteria and in plant protoplasts. - Corbin, D R (1994)
We cloned and sequenced structural gene choM, which encodes an insecticidally active cholesterol oxidase in Streptomyces sp. strain A19249. The primary translation product was predicted to be a 547-amino-acid protein whose first 43 amino acids constitute a secretory signal peptide. Expression of the gene with the signal sequence in Escherichia coli resulted in production of a protein that had enzymatic and insecticidal properties which were indistinguishable from those of the cholesterol oxidase secreted by Streptomyces sp. strain A19249. Expression of the gene with or without the signal sequence in tobacco protoplasts resulted in production of an enzymatically active cholesterol oxidase.